INVESTIGATION OF CONVENTIONAL AND ASPHALTIC UNDERLAYMENT TRACK BEHAVIORS SUBJECTED TO FREIGHT TRAIN LOAD: MECHANISTIC APPROACH - Setiawan, Dian M. (Journal of Applied Engineering Science, 2022)
The load characteristics in terms of the carrying capacity and the train operation speed limit Indonesia’s conventional track capability. In this study, the behaviors of Indonesia’s conventional tracks and the proposed asphaltic underlayment tracks under cyclic loading conditions of the low-speed Babaranjang (long-chain coal) freight trains have been evaluated using the finite element package Abaqus/CAE considering linear elastic behavior of materials. The numerical modeling was applied on three different layer thicknesses of sub-ballast in Indonesia’s conventional tracks and three different layer thicknesses of asphalt in asphaltic underlayment tracks to investigate the vertical compressive stress, horizontal-vertical-maximum strain, and deformation behaviors. According to the numerical simulation, the measurements indicate that the asphaltic underlayment tracks are superior to Indonesia’s conventional tracks. Furthermore, a 15 cm of asphalt layer in the asphaltic underlayment tracks demonstrates promising performance in the future of Indonesia’s railway systems. The asphaltic underlayment tracks are expected to serve the heavier and higher speed Babaranjang freight trains with longer service life and lower life cycle cost than Indonesia’s conventional tracks.